Utilization of Technology-Based Learning Media in Online Arabic Language Learning at Annajm Academy - Kosim, Nanang (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2024)
Online learning was initially used to facilitate students so they could study from home when the Covid-19 outbreak hit. Currently, everyone is getting used to online learning, and many institutions are starting to provide learning, one of which is Annajm Academy. However, there are many obstacles faced when learning online, among them, students often feel bored because their learning only focuses on looking at the screen. To make learning more interesting, interesting and varied learning media are available to support learning. This research aims to find out how much benefit technology-based teaching media has in supporting Arabic language learning at Annajm Academy. This research uses descriptive qualitative methods with the Miles and Huberman method in data analysis. The results obtained from this research are that there are several learning media used during Arabic language learning at Annajm Academy, including charts, YouTube videos, PowerPoint, online games and quizzes, and zoom as the main learning media. All of these media complement each other so that they can support learning to be more communicative even though it is carried out online.